Visions of architecture - Lees, Stephen (London : A & C Black, 2011)
'This fascinating study of the development of Western architecture focuses on a unique selection of 52 buildings--mostly from the last 300 years--examining why they have been designed in a particular way, the methods and materials used to construct them and their impact on the development of construction technology. The buildings have been chosen for their interesting history or design, or both, and are each beautifully illustrated as an architectural line drawing. They range from St Pancras Hotel in London to the Pennsylvania Railroad Station in New York City, to the Stoclet Palace in Brussels and the Acropolis in Athens. Drawing on a range of subject matters, from art through to politics, economics and religion, the author reveals a story about each of the buildings and the motivations of the societies, rulers or individuals that created them.'--Publisher's description.
Includes index.
Keywords: Architecture -- Sketch-books.; Architecture, Modern; Architecture -- Themes, motives